Economic evaluation of sintilimab plus chemotherapy vs. pembrolizumab plus chemotherapy for the treatment of first-line advanced or metastatic squamous NSCLC - Chen, Pingyu; Wang, Xintian; Zhu, Shengwen; Li, Hongchao; Rui, Mingjun; Wang, Yingcheng; Sun, Haikui; Ma, Aixia (Frontiers in Public Health, 2022)
Background and Objective: Sintilimab has superior efficacy and safety in patients with advanced or metastatic squamous non-small cell lung cancer (NSCLC), but its cost-effectiveness in China is unclear. This study is to evaluate the cost-effectiveness of sintilimab plus chemotherapy versus pembrolizumab plus chemotherapy for locally advanced or metastatic squamous NSCLC in China. Methods: From the perspective of the Chinese health system, the partitioned survival model with three health states was established in a 3-week cycle and a lifetime time horizon. The two-stage method was used to estimate the overall survival hazard rations to avoid the bias by crossover design in Orient-12 and Keynote-407 studies. The anchored matching adjusted indirect comparison method (MAIC) was used for indirect comparison based on the individual patient data from Orient-12 and public published Keynote 407 study due to the lack of head-to-head clinical trials. Only direct medical costs were included, and utilities were derived from the published literatures in base-case analysis. Sensitivity analysis was also performed to verify the robustness of the model results. In addition, the scenario analysis where the utilities were derived from the QLQ-C30 scale in Orient-12 by mapping to the EQ-5D-5L was carried out to explore the uncertainty of results. Results: Compared with the pembrolizumab, sintilimab incurred lower lifetime cost (12,321 vs. 36,371) and yielded less Quality-adjusted life-years (QALYs) (0.9902 vs. 1.0085), which resulted in an incremental cost-effectiveness ratio (ICER) of 1,314,208/QALY. Sintilimab strategy is a cost-effectiveness option under the willingness-to-pay (WTP) of 1-3 times the GDP per capita in China (11,250/QALY 33,749/QALY). The utility value of the post-progression was the most drivers in the deterministic sensitivity analysis (DSA) . According to the probabilistic sensitivity analysis (PSA), sintilimab was 100% cost-effective when the WTP was 1-3 times of China’s per capita GDP. The results of the scenario analysis showed that sintilimab group obtained more QALYs (1.2319 vs. 1.1815) and lower costs (12,321 vs. 36,371), which implied that the sintilimab + chemotherapy may dominate the pembrolizumab + chemotherapy. Conclusion: Compared with pembrolizumab + chemotherapy, sintilimab + chemotherapy is more cost-effective for first-line treatment in Chinese patients with locally advanced or metastatic squamous NSCLC.